PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SISWA PADA MATA PELAJARAN IPA KELAS IV DI SDN REJENI KECAMATAN KREMBUNG KABUPATEN SIDOARJO - Yulis Indriyani, ; Supriyono, (Pendidikan Sekolah Dasar, 2011)
The purpose in this research is to describing teachers activities in the learning implementation with inquiry learning model on science at fourth class. Describing the process skill, knowing the result of students learning process by the inquiry learning model, and describe student responsibility with inquiry implementation. This research is actually using classroom action research. The researches have been hold in two cycles, each cycles consisted of twice meeting, and through four steps are planning, observation, action and reflection. The subject of this research is student of 4th grade which has 26 students. The research will be held at SDN Rejeni Krembung Sidoarjo Data in this research was found by observation, questions and examination. The research uses descriptive qualitative analysis techniques. By the inquiry learning model was known in first cycle 72% for teacherâs activity later 86% in second cycle. The studentâs process skill equals 71% first and 82% in second cycle. Student activity equals 73% in first and 84% in second, the result of student examination in first cycle known 73% and 85% for second, and the interesting student in inquiry implementation equals 89%. All of the result has been taken equals 80% in succeeded and research result also showed increased each steps. Based on the description above, it can be concluded that by using inquiry learning model increase studentâs science process skill at fourth class in SDN Rejeni Krembung Sidoarjo.